Menumbuhkan Rasa Cinta terhadap Ilmu Keagamaan di Kalangan Anak-Anak Montasik, Aceh Besar - Umami, Riza; Ahmadian, Hendri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This community service observes and describes the application of the values ​​of religious knowledge to children in Reudeup Village, Montasik District, Aceh Besar District and explains how to foster children's love attitudes towards religious knowledge in the village. The results of this study indicate that the implementation of religious knowledge Most of the children in Reudeup Village went well, although a few of these children were still lacking in religious matters. Some of the factors that influence the lack of love of children towards religious knowledge in Reudeup Village, Montasik, Aceh Besar District include environmental influence, technology addiction, lack of spirituality, and lack of parental supervision, and children spend more time playing.